Bodega de datos y olap en unicauca virtual (2006)
The analysis of information has become one of the most important processes in major enterprises which manage a high number of customers. These Enterprises have found in the information generated by its own systems, valuable knowledge that might help to improve inner processes, customer relationship, competitiveness, cost cutting and revenue increase, etc. However, not only the major enterprises with industrial process and great quantity of customer, find the analysis of information; useful there are successful cases this kind of technology in other areas like transport, health, biology, chemistry, genetic, and education. This is why University of Cauca, sponsored by The Information Technology Group and Colciencias, has begun a project that implements a Decision Support System (DSS), that let directives and teachers of Unicauca Virtual, use the data warehouse potentiality and OLAP technologies to analyze information generated between students and the Learning Management System (LMS) of Unicauca Virtual. This article, present the development processes of this project emphasizing in modeling and construction of the data warehouse in the Oracle 10g Release2 database engine.